Literature - Li, Chunyu (Chinese culture series, 2014)
This book is the English version of Chinese Culture: Literature, which briefly introduces the development of Chinese culture in all ages for thousands of years. The book centers on the key writers and their works and pays attention to the introduction and analysis of specific writers and their works so that readers can get a relatively comprehensive and true feeling on Chinese literature. It helps readers to understand the living conditions and the inner spiritual world of Chinese people concerned and reflected in the literature works from the perspective of literature.